Paradigm Shift in Teaching Methodologies-Improved Knowledge of Faculty and Students - Radhika Devi, V. (Journal of Engineering Education Transformations, 2018)
The approach to science and engineering education in engineering colleges is slowly shifting its focus towards problem solving, innovation and creativity. Curricular and assessment methods are adapted that encourage critical thinking, open ended problem solving and creativity, which were previously built around teacher-centered lecture rooms that focused on information acquisition, memorization and regurgitation at closed book examination. This study examines the paradigm shift in teaching methodologies and analyses, the strengths and weaknesses in their implementation and also empowering the faculty with pedagogical methods. Further, it strives to capture teachers’ readiness to improve their professional skills and responsive practices as a form of accountability for their teaching and students’ learning; the two aspects that are increasingly being judged by various stakeholders. The overarching aim of introducing certain changes in teaching methodologies was to facilitate the development of faculty leadership in science and engineering education to introduce innovation and creativity into science and engineering education.